Road as morphological element of the town - Drozg, Vladimir (Journal for Geography, 2020)
Road as morphological element of town structure have so far not often been the subject of research in urban geography. The paper brings an example of interpretation the road from morphological point of view. Roads are multi-functional objects; in addition to their technical role, they play an important social, economic and formative role. Ptujska street in Maribor was a case study for this approach.
Keywords: urban geography; linear space; road; Ptujska cesta; Tezno; Maribor